Generic Platform to Generate Educational Components - Aarab, Yassine; Aknin, Noura; Benkaddour, Abdelhamid (Transactions on Engineering and Computing Sciences, 2017)
In this research, we will present all the concepts necessary for the implementation of a warehouse of educational components. We define three classes of educational components: Learning components, services components and technical components. We built a metadata schema to describe them. We will study the warehouse architecture and how the actors interact with it. We will also see the features implemented at the indexing and search system that integrates. The aim is to clarify the strategic solutions we have adopted to create a generic platform, adaptable and scalable. The instantiation of this platform provides the Educational Component Repository.